Analisis Kekuatan Mekanik Material Komposit Berserat Sabut Kelapa yang Berpeluang Diaplikasikan pada Pembuatan Spakbor Sepeda Motor - Darwis Saragih; Muhammad Yusuf Rahmansyah Siahaan; Rakhmad Arief Siregar (Universitas Medan Area, 2021)
Utilization of coconut fiber has attracted researchers to determine the mechanical properties of coconut fiber including the value of tensile strength, strain and modulus of elasticity. This study used variables 0 fiber, 5 fiber and 11 coconut fiber then the ratio between the matrix and the catalyst was 10:1 ml. In this study, the material used in the manufacture of composite materials is a type of polyester resin with a catalyst and the reinforcing material is coconut fiber. The composite will be made using the ASTM D 3039M-14 standard with a specimen size of 175 mm x 25 mm x 2 mm. The mold is made of glass and shaped to size using green double-sided foam tape. This tensile testing site was carried out at the Impact and Fracture Research Center, University of North Sumatra. Based on the analysis that has been carried out on the results of the tensile test, it includes looking for the value of tensile stress, yield strength, modulus of elasticity and point of fracture strain. With this test, the highest average tensile stress value is found in variable 5 coconut fiber with a value of 44,076 MPa. While the average value of yield strength is found in the 5 fiber variable with a value of 26,460 MPa, the largest average elastic modulus value is found in the 0 fiber variable of 1360 MPa. In this study, the comparison of the strength of the coconut fiber composite was uneven, this was due to the imperfect shape and process of making the specimen so that the fracture that occurred during the tensile test did not fully occur in the middle of the specimen object.